Screening of CEST MR Contrast Agents - Song, Xiaolei (2011)
There has been a tremendous amount of interest in developing new MR contrast agents for cellular and molecular imaging applications such as the visualization of tumors, highlighting areas of angiogenesis, highlighting of contrast agent-labeled therapeutic stem cells, and highlighting of contrast agent-labeled drug delivery vehicles. The contrast properties of paramagnetic and super-paramagnetic relaxation-based agents have allowed MR imaging to be used as a tool for all of the above applications. However, a new class of MR contrast agents, chemical exchange saturation transfer (CEST) agents, provides additional features such as (1) the ability to highlight multiple biological events at once within an image through the distinguishability of the different CEST contrast agents, (2) the ability to toggle the contrast “off-to-on” by applying a saturation pulse, and (3) potentially providing more information about the environment surrounding the contrast agent such as the pH or concentration of metabolites. In this chapter, we will focus on the methods which can be used in terms of acquisition schemes and hardware to screen these agents through MR imaging.